Hubungan Usia, Jenis Kelamin dan Status Anemia dengan Fungsi Kognitif pada Lanjut Usia - Riza Firdaus (Faletehan Health Journal, 2020)
The decline in cognitive function greatly influences the quality of life of the elderly. Factors that influence are physiological, psychological and environmental factors. This study aims to determine the relationship of age, sex and anemia status with cognitive function in the elderly. This study was an observational analytic study with a cross-sectional design. This research was conducted at Weningha Wening Wardoyo Semarang. The number of samples obtained was 51 elderly who were elected with a total sampling technique. The dependent variable was cognitive function and the independent variables were age, gender and anemia status. The examination of cognitive function was measured by the Mini-Mental State Examination (MMSE) instrument and anemia status examination using a haemometer with the Sahli method. The data analysis used was the Chi-Square test. Results: The risk of age <75 years increased the risk of normal cognitive function (OR = 6.480; 95% CI 1.844-22,769; p = 0.002), male gender (OR = 2.357; 95% CI 0.688- 8.075; p = 0.167) and mild anemia (OR = 2,821; 95% CI 0.831-9,577; p = 0.091). This study concludes that cognitive function in the elderly is influenced by age, gender and anemia status.